Psychosocial Factors Associated With Resilience Among Iranian Nurses During COVID-19 Outbreak - Afshari, Davood; Nourollahi-darabad, Maryam; Chinisaz, Niloofar (Frontiers in Public Health, 2021)
Background: In the face of COVID-19, healthcare workers need to cope with the ongoing stressors at play and keep psychological distress at a minimum level. This study examined the psychosocial and demographic factors associated with nurse's resilience in the hospitals of Ahvaz that is one of the top cities infected with COVID-19 in Iran. Methods: The present cross-sectional study was conducted on 387 Iranian nurses in Ahvaz city. For data collection purposes, three online questionnaires (including Copenhagen Psychosocial, Demographic, and Connor–Davidson Resilience Scale) were distributed among the participants. Results: The mean resilience score was equal to 61.8 ± 14.8 for 387 nurses. Resilience had a statistically significant negative correlation with quantitative demand (r = −0.273, P < 0.008), work pace (r = −0.262, P < 0.011), emotional demand (r = −0.226, P < 0.030), stress (r = −0.458, P < 0.000), and burnout (r = −0.287, P < 0.005). Multiple linear regression analysis indicated that stress, job satisfaction, burnout and age were the main predictors of nurses' resilience during the (COVID-19) pandemic (R2 = 0.45). Conclusions: We identified psychosocial and demographic predictive factors that may contribute to greater resilience among nurses during the COVID-19 outbreak. The findings of this study can be used to implement psychosocial interventions to amplify the resilience of medical staff during the COVID-19 outbreak.